Photon excitation of the third molecular continuum in solid krypton - Ogurtsov, A. N.; Savchenko, E. V.; Becker, J.; Runne, M.; Zimmerer, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
Luminescence study of the near-ultraviolet continuum in nominally pure solid krypton under selective excitation by synchrotron radiation is presented. Intrinsic nature of the emission has been established. Clear threshold behavior at the band gap energy reveals the key role of the electron-hole pairs in a population of the continuum forming states.